A vision of Macau’s football through the symbolic legacy of the Portuguese presence - Gouveia, C. (International Journal of the History of Sport, 2021)
This paper analyses the sociocultural background, and the nature of the cultural legacy of the Portuguese, in the diffusion and promotion of football in Macau. The paper seeks to examine why men’s football in Macau’s remains poorly developed at domestic, regional and international levels. Many factors could explain this lack of development, ranging from the limited degree of organizational specialization inherited from the Portuguese administration, problems regarding implementing rules and tournament organization, the lack of sports facilities, and the tension between the national governing body and the national team athletes. Nevertheless, there has also been some important progress, such as the recruitment of young footballers and the inclusion of local Portuguese talented players. These developments are discussed in a multidisciplinary approach, based on academic literature and harnessing comprehensive documentary analysis derived from official documents and website information of sports associations.